PEMBUATAN ELEKTRODA SELEKTIF ION KADMIUM TIPE KAWAT TERLAPIS BERMEMBRAN D2EHPA - Putra, Dedi Arta; Atikah, Atikah; Sulisyarti, Hermin (Jurusan Kimia, FMIPA Universitas Brawijaya, 2013)
ABStract Preparation of coated wire cadmium(II) ion selective electrodes Cd(II) CWE) membranous Di (2-Ethyl Hexyl) Phosporic Acid (D2EHPA) has been done to obtain the optimum membrane composition ratio and optimum soaking time that produce cadmium(II) CWE have Nerntstian character. Preparation of cadmium(II) CWE was conducted by three kinds of membrane composition comprising an active ingredient D2EHPA, matrix material consist of polyvinylchloride (PVC) polymer and plasticizer dibutylphtalate (DBP) dissolved in tetrahydrofuran (THF) solvent with a ratio of 1:3 by weight/volume. Potential measurements made​​ in the CdCl2test solution in the concentration range10-8-10-1M at pH 5. Optimization of time soaking in a solution of CdCl2 0.1M performed at optimum membrane composition in the time range of 0-80 minutes with 10 minutes intervals. The results showed that the optimum composition of the membrane is a membrane with the composition ratio of D2EHPA : PVC : DBP = 16 : 28 : 56 produces Nernstian properties with prices Nernst factor of 27.26mV/decade of concentration needed optimum soaking time in a solution of CdCl2 0.1M for 20 minutes. Key words: cadmium CWE, D2EHPA, membrane, potentiometry